Making of Pressure Springs From Low Carbon Steel St 37 Material as an Alternative to Standard Pressure Springs in Mold Construction Through Solid Carburation Processes - Heri Setiawan (Asian Journal of Social and Humanities, 2023)
Compression Spring is one of standard components type that are widely used in machinery construction, as well as in mold construction that serves to restore the position of the ejector mould into position. This study aims to find alternative materials for standard compression spring using specimen test of low carbon steel St 37 in the form of a compression spring is made by using coiling process followed to heat treatment processes such as pack carburizing, hardening, quenching and tempering. To ensure the quality process, the tests should be done in the laboratory such us the hardness test, the distribution of hardness, microstructure and deflection of the spring test. The pack carburizing is done at a temperature of 925ºC with a holding time of 2.5 hours, followed by a case hardening process at a temperature of 870ºC with a holding time of 12.5 minute and quenched on medium oil and tempered at a temperature of 350ºC. The results of this research show that the method used to generate the average value of 456.57 HV and have ? – martensite microstructure and also the compression spring deflection average value of 18.625 N/mm on 613.9 N. Those data approaches the compression spring standard value of hardness, microstructure and deflection. Based on the data analysis, low carbon steel St 37 can be used as alternative material for standard compression spring.